Participatory approaches to identify and test gender-responsive seed information pathways - Tenneti, Suchaita; Kori, Pooja; Puskur, Ranjitha; Nagubandi, Uday; Reddy, Yadava; Khan, Afreen (CGIAR System Organization, 2023)
This technical report comprises the results of a formative, exploratory study conducted to understand farmers’ preferences about which seed information pathways are most effective to provide them information on quality seeds of improved varieties. It is a part of a larger project aimed to identify and test out gender-responsive seed information and delivery pathways. While this particular exploratory study focused predominantly on seed information pathways, it is planned that future studies within this project shall consider the interlinkages between seed information and delivery pathways. The study incorporates an intersectional gender and social inclusion lens to understand farmers’ preferences for seed information pathways. It also adopts a participatory approach to seek farmers’ assessment of communication products designed to provide information on seeds of new varieties and aims to incorporate this feedback in improving the effectiveness of the products.